Makna Kata Disiplin Berdasarkan Amsal 19:18 dan Implementasinya bagi Orang Tua Kristen dalam Mendidik Anak - Suranto; Rinawaty (Sekolah Tinggi Teologi Anugrah Indonesia, 2025)
Child discipline is a crucial parental responsibility in forming a generation of character and reverence for God, but its practice often falls into two extremes: harsh discipline potentially harming the child or an overly permissive approach that leaves children without moral guidance. This biblical exegetical research on Proverbs 19:18 aims to analyze the concept of child discipline from a biblical perspective, using a comprehensive interpretive method that considers socio-theological context. The research results show that true discipline is an educational process based on love, encompassing instruction, wise correction, and educational consequences, focusing on forming children's spiritual character from an early age through a holistic approach that avoids violence and directs children towards wisdom and obedience to God.